A sulfide electrolyte and its preparation method and all-solid-state battery

By using oxygen-containing atmosphere to cool down the air stability and phase purity of the sulfide all-solid battery during the preparation process of the sulfide electrolyte, the air stability and phase purity of the sulfide all-solid battery is solved, and higher air stability and phase purity are achieved, which is suitable for assembling all-solid battery in a dry environment.

CN118841623BActive Publication Date: 2025-04-25四川新能源汽车创新中心有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410808110.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-21
Publication Date
2025-04-25
Estimated Expiration
2044-06-21

AI Technical Summary

Technical Problem

The air stability of sulfide all-solid state batteries is poor, and there are phase purity problems during the production process, resulting in batch unstable.

Method used

During the preparation of the sulfide electrolyte, the cooling treatment is carried out after the calcination treatment, and an oxygen-containing atmosphere is set at at least part of the cooling stage to oxidize active sulfur on the surface of the sulfide particles, increase the oxygen content, inhibit the precipitation of LiCl, and improve the phase purity.

Benefits of technology

The air stability and phase purity of the sulfide electrolyte are improved, and its water resistance and oxidation resistance are enhanced, so that all-solid secondary batteries can be directly assembled in a dry environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118841623B_ABST
    Figure CN118841623B_ABST
Patent Text Reader

Abstract

The present invention discloses a sulfide electrolyte and a preparation method thereof and an all-solid-state battery, and belongs to the technical field of solid-state battery electrolytes. The preparation method comprises: after a sulfide electrolyte precursor of argyrodite type is subjected to a roasting treatment, a sulfide electrolyte material obtained by the roasting treatment is subjected to a cooling treatment, and during the cooling treatment process, the atmosphere corresponding to at least part of the cooling stage is set to an oxygen-containing atmosphere. By setting the atmosphere of at least part of the cooling stage to an oxygen-containing atmosphere, the active sulfur on the surface of the sulfide particles can be oxidized, and the oxygen content on the surface of the particles is increased. At the same time, the above method can inhibit the precipitation of LiCl during the cooling process, and the phase purity of the material can be improved. In addition, the active sulfur at positions 4a and 4d on the particle surface reacts with oxygen during the cooling process, and the water resistance and oxidation resistance of the material can be improved, so that the assembly operation of the all-solid-state secondary battery can be directly performed in a dry environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state battery electrolytes, and in particular to a sulfide electrolyte and a preparation method thereof and an all-solid-state battery. Background Art

[0002] All-solid-state batteries are considered to have great commercial value due to their high energy density potential and excellent safety performance. In order to achieve the high energy density advantage of all-solid-state batteries and to achieve fast charging performance to a certain extent, sulfide electrolytes with high ion conductivity can be used, but sulfide all-solid-state batteries have poor stability in air. 7- n PS 6-n X n Sulfide solid electrolytes represented by LPSX (abbreviated as LPSX, where X is selected from Cl, Br or I, etc.) have an ionic conductivity of up to 10mS / cm, but they are extremely sensitive to moisture. Even when exposed to a low dew point of around -40°C, they will quickly react with moisture in the air to generate toxic H2S gas, greatly increasing the difficulty of producing LPSX system sulfide electrolytes. In addition, the production of sulfide electrolytes faces the problem of batch instability, which is structurally manifested as the easy appearance of LiCl impurities in the chlorine-rich system. The reason is the sensitivity of the sulfide electrolyte structure, which places strict requirements on the process conditions of the preparation process.

[0003] Therefore, how to solve the air stability and phase purity problems of sulfide electrolytes is the key issue that needs to be explored in the industrialization stage of sulfide electrolytes.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The object of the present invention is to provide a sulfide electrolyte and a preparation method thereof and an all-solid-state battery to solve or improve the above-mentioned technical problems.

[0006] The present invention can be implemented like this:

[0007] In a first aspect, the present invention provides a method for preparing a sulfide electrolyte, which comprises the following steps: after a argyrodite-type sulfide electrolyte precursor is calcined, the sulfide electrolyte material obtained by the calcination is cooled, and during the cooling process, the atmosphere corresponding to at least part of the cooling stage is set to an oxygen-containing atmosphere.

[0008] In an optional embodiment, the preparation of the argyrodite-type sulfide electrolyte precursor includes: mixing the preparation raw materials under a first inert atmosphere and ball milling; wherein the preparation raw materials include Li2S, P2S5 and LiX, and X is a halogen element.

[0009] In an alternative embodiment, X comprises at least one of Cl, Br and I.

[0010] In an optional embodiment, the first inert atmosphere includes a nitrogen atmosphere, an argon atmosphere, or a mixed atmosphere of hydrogen sulfide and argon;

[0011] In an optional embodiment, the first inert atmosphere is an argon atmosphere.

[0012] In an optional embodiment, the mass percentage of Li2S in the preparation raw material is 30% to 45%, the mass percentage of P2S5 in the preparation raw material is 40% to 45%, and the mass percentage of LiX in the preparation raw material is 15% to 30%.

[0013] In an alternative embodiment, the molar ratio of Li2S, P2S5 and LiX is 1.9:0.5:1.6.

[0014] In an optional embodiment, the rotation speed of the ball mill is 200 rpm to 500 rpm; and / or the ball milling time is 40 h to 60 h.

[0015] In an optional embodiment, the calcination process includes at least one of the following features:

[0016] Feature 1: The calcination temperature is 290°C to 938°C, preferably 450°C to 550°C;

[0017] Feature 2: The calcination time is 4 to 5 hours, preferably 4.5 hours;

[0018] Feature 3: The heating rate during the calcination process is 180℃ / h~200℃ / h;

[0019] Feature 4: Calcination is carried out under a second inert atmosphere;

[0020] Feature 5: The calcined argyrodite-type sulfide electrolyte precursor satisfies the requirement that the mass change of water contained in the argyrodite-type sulfide electrolyte precursor does not exceed 0.1 ppm for at least one consecutive hour.

[0021] In an optional embodiment, the calcination temperature is at least 400° C., and during the cooling process, at least the atmosphere corresponding to the stage where the temperature does not exceed 400° C. is set to an oxygen-containing atmosphere.

[0022] In an optional embodiment, during the cooling process, when the temperature drops to 380° C. to 430° C., the second inert atmosphere is adjusted to an oxygen-containing atmosphere.

[0023] In an optional embodiment, the ventilation time of the oxygen-containing atmosphere is 1 min to 60 min.

[0024] In an optional embodiment, the ventilation time of the oxygen-containing atmosphere is 5 min to 50 min.

[0025] In an optional embodiment, the oxygen-containing atmosphere is a mixed gas atmosphere of oxygen and an inert gas.

[0026] In an optional embodiment, in the mixed gas, the volume ratio of oxygen to inert gas is 0.05:1 to 0.5:1, preferably 0.1:1 to 0.3:1.

[0027] In an alternative embodiment, the inert gas is argon.

[0028] In an optional embodiment, the electrolyte material obtained after the cooling is completed is dried.

[0029] In an alternative embodiment, the drying is vacuum drying.

[0030] In an optional embodiment, the drying temperature is 75°C to 85°C.

[0031] In an optional embodiment, the drying time is 20 hours to 28 hours.

[0032] In a second aspect, the present invention provides a sulfide electrolyte prepared by the preparation method of any one of the aforementioned embodiments.

[0033] In a third aspect, the present invention provides an all-solid-state battery comprising the sulfide electrolyte of the aforementioned embodiment.

[0034] The beneficial effects of the present invention include:

[0035] The sulfide electrolyte preparation method provided by the present invention can oxidize the active sulfur on the surface of the sulfide particles by setting the atmosphere of at least part of the cooling stage to an oxygen-containing atmosphere, thereby increasing the oxygen content on the surface of the particles. At the same time, the above method can inhibit the precipitation of LiCl during the cooling process, and the phase purity of the material can be improved. In addition, the active sulfur at positions 4a and 4d on the particle surface reacts with oxygen during the cooling process, and the water resistance and oxidation resistance of the material can be improved. Even if it is processed in a dry environment, the material deteriorates less, so that the assembly operation of the all-solid-state secondary battery can be directly performed in a dry environment. The obtained sulfide electrolyte has high air stability, conductivity and phase purity, and can be used to prepare all-solid-state batteries with high energy density and conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0037] Figure 1 A result diagram of H2S release of the sulfide electrolyte provided in Examples 1 to 6 and Comparative Example 1 in the test examples in a dry room environment;

[0038] Figure 2 This is the XRD diagram of the sulfide electrolyte provided in Examples 1 to 6 and Comparative Example 1 in the Experimental Examples. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0040] The sulfide electrolyte, preparation method thereof and all-solid-state battery provided by the present invention are described in detail below.

[0041] The present invention provides a method for preparing a sulfide electrolyte, which comprises the following steps: after a sulfide electrolyte precursor of the argyrodite type is subjected to a calcination treatment, a sulfide electrolyte material obtained by the calcination treatment is subjected to a cooling treatment, and during the cooling treatment, the atmosphere corresponding to at least part of the cooling stage is set to an oxygen-containing atmosphere.

[0042] By setting the atmosphere of at least part of the cooling stage to an oxygen-containing atmosphere, the active sulfur on the surface of the sulfide particles can be oxidized, increasing the oxygen content on the surface of the particles. At the same time, the above method can inhibit the precipitation of LiCl during the cooling process, and the phase purity of the material can be improved. In addition, the active sulfur at positions 4a and 4d on the particle surface reacts with oxygen during the cooling process, and the water resistance and oxidation resistance of the material can be improved. Even if it is processed in a dry environment, the material deteriorates less, so that the assembly operation of the all-solid-state secondary battery can be directly carried out in a dry environment.

[0043] The molecular formula of the argyrodite-type sulfide electrolyte in the present invention is Li 7-n PS 6-n X n , referred to as LPSX. In the above molecular formula, X is selected from halogen elements, for example, at least one of Cl, Br and I. The value range of n can be 0 to 1.8.

[0044] In some optional ways, the preparation of the argyrodite-type sulfide electrolyte precursor includes: mixing the preparation raw materials under a first inert atmosphere, and ball milling; wherein the preparation raw materials include Li2S, P2S5 and LiX, and X is a halogen element, for example, it may include at least one of Cl, Br and I. Exemplarily, LiX may include at least one of LiCl, LiBr and LiI.

[0045] As an example, the mass percentage of Li2S in the raw material for preparation can be 30% to 45%, such as 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44% or 45%, etc., or other values ​​within the range of 30% to 45%. The mass percentage of P2S5 in the raw material for preparation can be 40% to 45%, such as 40%, 40.5%, 41%, 41.5%, 42%, 42.5%, 43%, 43.5%, 44%, 44.5% or 45%, etc., or other values ​​within the range of 40% to 45%. The mass percentage of LiX in the preparation raw material can be 15% to 30%, such as 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29% or 30%, etc., or other values ​​within the range of 15% to 30%.

[0046] In some specific embodiments, the sum of the mass percentages of Li2S, P2S5 and LiX in the above-mentioned raw materials is 100%.

[0047] In the present invention, the molar ratio of Li2S, P2S5 and LiX is Li 7-n PS 6-n X n Matching, for example, can be 1.9:0.5:1.6, etc.

[0048] In the present invention, the first inert atmosphere may illustratively but not limitatively include nitrogen atmosphere, argon atmosphere, a mixed atmosphere of hydrogen sulfide and argon, etc. In some typical embodiments, the first inert atmosphere is an argon atmosphere.

[0049] It should be emphasized that the ball milling process of the present invention is carried out under the first inert atmosphere. Although a certain oxygen atmosphere is controlled during the crushing and grinding of the sulfide material, the effect of introducing O atoms on the surface of the sulfide material can also be achieved, but during the high-energy ball milling process, the high energy density of the crushing process may cause the sulfide to undergo phase decomposition and precipitate LiCl. The present invention creatively completes the introduction of surface O atoms at a specific stage of cooling when the sulfide is still in a highly reactive state, and the surface lattice is stabilized at this time, thereby further stabilizing the phase and avoiding the phase decomposition of the sulfide.

[0050] In the present invention, ball milling can be performed in a planetary ball mill, and the rotation speed of the ball milling can be 200 rpm to 500 rpm, such as 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm or 500 rpm, or other values ​​within the range of 200 rpm to 500 rpm. The ball milling time can be 40 h to 60 h, such as 40 h, 45 h, 50 h, 55 h or 60 h, or other values ​​within the range of 40 h to 60 h.

[0051] Furthermore, the powdery argyrodite-type sulfide electrolyte precursor obtained by ball milling is subjected to a calcination treatment.

[0052] In some optional embodiments, the argentite-type sulfide electrolyte precursor subjected to the calcination treatment satisfies the requirement that the mass change of water contained in the argentite-type sulfide electrolyte precursor does not exceed 0.1 ppm for at least one consecutive hour.

[0053] By controlling this condition, it is possible to avoid the water brought into the argyrodite-type sulfide electrolyte precursor, which causes the material structure to change after calcination and makes it impossible to obtain a sulfide electrolyte.

[0054] For reference, the change of water content in the above-mentioned argyrodite-type sulfide electrolyte precursor can be carried out in the following way: the powdered argyrodite-type sulfide electrolyte precursor obtained by ball milling is placed in a glove box filled with protective gas (such as argon), and the water content fluctuation value in the glove box is observed. When the water content is lower than 0.1ppm for at least one hour, the corresponding powdered argyrodite-type sulfide electrolyte precursor is collected in an open quartz crucible and sealed for standby use. The open quartz crucible is transferred to a tube furnace for calcination.

[0055] In some optional ways, the roasting temperature can be 290°C to 938°C, such as 290°C, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C or 938°C, etc. In some typical embodiments, the roasting temperature is 450°C to 550°C, such as 450°C, 455°C, 460°C, 465°C, 470°C, 475°C, 480°C, 485°C, 490°C, 495°C, 500°C, 505°C, 510°C, 515°C, 520°C, 525°C, 530°C, 535°C, 540°C, 545°C or 550°C, etc., and can also be other values ​​within the range of 450°C to 550°C. In some more typical embodiments, the calcination temperature is 480°C to 490°C, such as 480°C, 481°C, 482°C, 483°C, 484°C, 485°C, 486°C, 487°C, 488°C, 489°C or 490°C, etc., and may also be other values ​​within the range of 480°C to 490°C.

[0056] If the calcination temperature is too low or too high, the crystallinity and conductivity of the sulfide electrolyte will be affected.

[0057] In some optional embodiments, the calcination time can be 4 to 5 hours, such as 4 hours, 4.1 hours, 4.2 hours, 4.3 hours, 4.4 hours, 4.5 hours, 4.6 hours, 4.7 hours, 4.8 hours, 4.9 hours or 5 hours, or other values ​​within the range of 4 to 5 hours. In some typical embodiments, the calcination time can be 4.5 hours.

[0058] Similarly, if the calcination time is too short or too long, it will also affect the crystallinity and conductivity of the sulfide electrolyte.

[0059] In some optional embodiments, the heating rate during the roasting process can be 180℃ / h to 200℃ / h, such as 180℃ / h, 185℃ / h, 190℃ / h, 195℃ / h or 200℃ / h, or other values ​​within the range of 180℃ / h to 200℃ / h.

[0060] If the heating rate is lower than 180°C / h, it is easy to cause excessive energy consumption; if the heating rate is higher than 200°C / h, it is easy to cause incomplete crystallization.

[0061] The above calcination process is all carried out under the second inert atmosphere. Preferably, the second inert atmosphere of the calcination process is consistent with the first inert atmosphere of the ball milling process.

[0062] Furthermore, the sulfide electrolyte material obtained by the calcination treatment (which may be referred to as "sulfide electrolyte coarse powder material") is subjected to a cooling treatment.

[0063] In the present invention, during the cooling process, at least part of the cooling stage corresponds to an oxygen-containing atmosphere. In some optional ways, the entire cooling process may be carried out in an oxygen-containing atmosphere; in other optional ways, part of the cooling stage may be carried out in the second inert atmosphere, and part of the cooling stage may be carried out in an oxygen-containing atmosphere.

[0064] The above-mentioned cooling treatment may be, illustratively but not limitatively, natural cooling.

[0065] In some embodiments, the calcination temperature is at least 400°C, and during the cooling process, at least the atmosphere corresponding to the stage where the temperature does not exceed 400°C is set to an oxygen-containing atmosphere. That is, the atmosphere can be adjusted to an oxygen-containing atmosphere before the temperature drops to 400°C; in addition, the atmosphere can be adjusted to an oxygen-containing atmosphere when the temperature drops to 400°C.

[0066] In some preferred embodiments, during the cooling process, when the temperature drops to 380° C. to 430° C., the second inert atmosphere is adjusted to an oxygen-containing atmosphere. This solution results in better phase purity and air stability of the resulting sulfide electrolyte.

[0067] In the present invention, the oxygen-containing atmosphere may be a pure oxygen atmosphere or an atmosphere in which oxygen is mixed with other inert gases.

[0068] In some preferred embodiments, the oxygen-containing atmosphere is a mixed gas atmosphere of oxygen and an inert gas, and the phase purity and air stability of the sulfide electrolyte obtained in this scheme are better. In this mixed gas, the volume ratio of oxygen to inert gas can be 0.05:1 to 0.5:1, such as 0.05:1, 0.1:1, 0.15:1, 0.2:1, 0.25:1, 0.3:1, 0.35:1, 0.4:1, 0.45:1 or 0.5:1, etc., or other values ​​within the range of 0.05:1 to 0.5:1. In some more typical embodiments, the volume ratio of oxygen to inert gas is preferably 0.1:1 to 0.3:1. Similarly, the inert gas can be argon, nitrogen, a mixed gas of hydrogen sulfide and argon, etc., preferably argon.

[0069] It should be noted that if the volume ratio of oxygen to inert gas in the above-mentioned oxygen-containing atmosphere is less than 0.05:1, it is not conducive to the formation of an oxygen layer on the surface of the particles; if the volume ratio of oxygen to inert gas is greater than 0.5:1, it is not conducive to improving the phase purity of the sulfide electrolyte.

[0070] In some optional embodiments, the ventilation time of the oxygen-containing atmosphere can be 1 min to 60 min, such as 1 min, 2 min, 5 min, 8 min, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min, etc., or other values ​​within the range of 1 min to 60 min. In some typical embodiments, the ventilation time of the oxygen-containing atmosphere can be 5 min to 50 min.

[0071] Furthermore, the electrolyte material obtained after the cooling process is completed may be dried or may not be dried.

[0072] For example, drying can be performed by vacuum drying.

[0073] In some optional embodiments, the drying temperature can be 75°C to 85°C, such as 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C or 85°C, or other values ​​within the range of 75°C to 85°C.

[0074] In some optional embodiments, the drying time can be 20 hours to 28 hours, such as 20 hours, 21 hours, 22 hours, 23 hours, 24 hours, 25 hours, 26 hours, 27 hours or 28 hours, or other values ​​within the range of 20 hours to 28 hours.

[0075] After drying, the granules can be sized through a sieve to obtain a sulfide electrolyte fine powder. The sieve can be a stainless steel sieve with a sieve hole diameter of 1 μm to 20 μm, which is exemplary but not limiting.

[0076] As mentioned above, the present invention increases the oxygen content on the surface of the electrolyte particles by introducing a small amount of oxygen during at least part of the cooling stage during the material preparation process, thereby inhibiting the dissolution of LiCl during the cooling stage and improving the phase purity of the material. In addition, the oxygen content on the surface of the particles is increased by the above treatment, and the water resistance and oxygen resistance of the material itself are significantly improved. Even when the all-solid-state secondary battery is directly assembled in a drying chamber, the amount of H2S released is relatively small.

[0077] Correspondingly, the present invention provides a sulfide electrolyte, which is prepared by the above preparation method.

[0078] The sulfide electrolyte has less impurity content, higher phase purity, excellent air stability, and less H2S release when exposed in a drying chamber.

[0079] In addition, the present invention also provides an all-solid-state battery, which contains the sulfide electrolyte of the above-mentioned embodiment. The all-solid-state battery can have higher energy density and electrical conductivity.

[0080] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0081] Example 1

[0082] This embodiment provides a sulfide electrolyte of the argyrodite type, the molecular formula of which is Li 5.4 PS 4.4 Cl 1.6 .

[0083] The electrolytic preparation of the argyrodite-type sulfide comprises:

[0084] S1: Preparation of argyrodite-type sulfide electrolyte precursor.

[0085] Weigh 10 g of Li2S powder, P2S5 powder and LiCl powder as raw materials for preparation. 5.4 PS 4.4 Cl 1.6 The molar ratio of the elements in the raw material is such that the molar ratio of Li2S powder, P2S5 powder and LiX powder in the raw material is 1.9:0.5:1.6. Accordingly, the mass percentage of Li2S powder in the raw material is 32.76%, the mass percentage of P2S5 powder in the raw material is 41.75%, and the mass percentage of LiX powder in the raw material is 25.49%.

[0086] The raw materials were put into a ball mill, the mass ratio of the raw materials to ZrO2 ball milling beads was 1:40, and argon protective gas was introduced into the ball mill. The ball milling speed was 400 rpm, and the ball milling was paused for 30 minutes every 5 hours, and the material was collected after a total of 50 hours of ball milling.

[0087] The entire process of preparing the above ingredients and ball milling is completed in a glove box with a water content of less than 0.1 ppm and an oxygen content of less than 1 ppm.

[0088] All the precursor raw materials collected were placed in a high-speed crusher for crushing. The threaded blades in the crusher cavity rotated at high speed, and the blade speed was controlled to be 21000rpm. After every 10 minutes of crushing, there was a 30-minute pause, and the total crushing time was 30 minutes (the whole crushing process was completed in a glove box with a water content of less than 0.1ppm and an oxygen content of less than 1ppm). The dry materials that were finally crushed were collected and placed in a glove box. After ensuring that the water content in the glove box was less than 0.1ppm for at least one hour, they were flattened in an open quartz crucible.

[0089] S2: calcining the argyrodite-type sulfide electrolyte precursor.

[0090] The quartz crucible in S1 was transferred from the glove box to a tube furnace for high-temperature calcination in the tube furnace. Argon protective gas was introduced into the tube furnace at 1 L / min, and the temperature was raised to 480°C at a heating rate of 200°C / h, and kept at this temperature for 4.5 hours to obtain a sulfide electrolyte coarse powder.

[0091] S3: Cooling the sulfide electrolyte coarse powder.

[0092] After the calcination, the mixture was cooled naturally. When the temperature dropped to 400°C, the carrier gas was replaced from pure argon to a mixture of oxygen and argon at a flow rate of 1 L / min. The volume ratio of oxygen to argon in the mixture was 1:10. The ventilation time was 5 min. After the calcination, the mixture was cooled naturally until it reached room temperature. The mixture was granulated with a stainless steel mesh with a pore size of 1 μm to obtain a fine powder of sulfide electrolyte (i.e., argyrodite-type sulfide electrolyte).

[0093] Example 2

[0094] The difference between this embodiment and embodiment 1 is that in S3, the ventilation time is 10 minutes.

[0095] Example 3

[0096] The difference between this embodiment and embodiment 1 is that in S3, the ventilation time is 20 minutes.

[0097] Example 4

[0098] The difference between this embodiment and embodiment 1 is that in S3, the volume ratio of oxygen to argon in the mixed gas is 1:5.

[0099] Example 5

[0100] The difference between this embodiment and embodiment 1 is that in S3, the volume ratio of oxygen to argon in the mixed gas is 1:5, and the ventilation time is 10 minutes.

[0101] Example 6

[0102] The difference between this embodiment and embodiment 1 is that in S3, the volume ratio of oxygen to argon in the mixed gas is 1:5, and the ventilation time is 20 minutes.

[0103] Example 7

[0104] The difference between this embodiment and embodiment 1 is that in S2, the calcination temperature is 450°C.

[0105] Example 8

[0106] The difference between this embodiment and embodiment 1 is that in S2, the calcination temperature is 470°C.

[0107] Example 9

[0108] The difference between this embodiment and embodiment 1 is that in S2, the calcination temperature is 490°C.

[0109] Example 10

[0110] The difference between this embodiment and embodiment 1 is that in S2, the calcination temperature is 550°C.

[0111] Embodiment 11

[0112] The difference between this embodiment and embodiment 1 is that in S2, the calcination temperature is 600°C.

[0113] Example 12

[0114] The difference between this embodiment and embodiment 1 is that in S3, the ventilation duration is 1 minute.

[0115] Embodiment 13

[0116] The difference between this embodiment and embodiment 1 is that in S3, the ventilation time is 50 minutes.

[0117] Embodiment 14

[0118] The difference between this embodiment and embodiment 1 is that in S3, the ventilation time is 60 minutes.

[0119] Embodiment 15

[0120] The difference between this embodiment and embodiment 1 is that in S3, the volume ratio of oxygen to argon in the mixed gas is 0.05:1.

[0121] Example 16

[0122] The difference between this embodiment and embodiment 1 is that in S3, the volume ratio of oxygen to argon in the mixed gas is 0.3:1.

[0123] Embodiment 17

[0124] The difference between this embodiment and embodiment 1 is that in S3, the volume ratio of oxygen to argon in the mixed gas is 0.5:1.

[0125] Embodiment 18

[0126] The difference between this embodiment and embodiment 1 is that in S2, when the temperature drops to 480°C, the corresponding atmosphere is set to an oxygen-containing atmosphere.

[0127] Embodiment 19

[0128] The difference between this embodiment and embodiment 1 is that the entire cooling process is in an oxygen-containing atmosphere.

[0129] Embodiment 20

[0130] This embodiment provides a sulfide electrolyte of the argyrodite type, the molecular formula of which is Li 5.5 PS 4.5 Cl 1.5 .

[0131] The electrolytic preparation of the argyrodite-type sulfide comprises:

[0132] S1: Preparation of argyrodite-type sulfide electrolyte precursor.

[0133] Weigh 10 g of Li2S powder, P2S5 powder and LiCl powder as raw materials for preparation. 5.5 PS 4.5 Cl 1.5 The molar ratio of the elements in the raw material is such that the molar ratio of Li2S powder, P2S5 powder and LiCl powder in the raw material is 2:0.5:1.5. Accordingly, the mass percentage of Li2S powder in the raw material is 34.44%, the mass percentage of P2S5 powder in the raw material is 41.70%, and the mass percentage of LiCl powder in the raw material is 23.86%.

[0134] The raw materials were put into a ball mill, the mass ratio of the raw materials to ZrO2 ball milling beads was 1:40, and nitrogen protective gas was introduced into the ball mill. The ball milling speed was 200 rpm, and the ball milling was paused for 30 minutes every 5 hours, and the material was collected after a total of 60 hours of ball milling.

[0135] The entire process of preparing the above ingredients and ball milling is completed in a glove box with a water content of less than 0.1 ppm and an oxygen content of less than 1 ppm.

[0136] All the precursor raw materials collected were placed in a high-speed crusher for crushing. The threaded blades in the crusher cavity rotated at high speed, and the blade speed was controlled to be 21000rpm. After every 10 minutes of crushing, there was a 30-minute pause, and the total crushing time was 30 minutes (the whole crushing process was completed in a glove box with a water content of less than 0.1ppm and an oxygen content of less than 1ppm). The dry materials that were finally crushed were collected and placed in a glove box. After ensuring that the water content in the glove box was less than 0.1ppm for at least one hour, they were flattened in an open quartz crucible.

[0137] S2: calcining the argyrodite-type sulfide electrolyte precursor.

[0138] The quartz crucible in S1 was transferred from the glove box to a tube furnace and calcined at high temperature in the tube furnace. Nitrogen protective gas was introduced into the tube furnace at 1 L / min, and the temperature was raised to 290°C at a heating rate of 180°C / h and kept at this temperature for 5 hours to obtain a sulfide electrolyte coarse powder.

[0139] S3: Cooling the sulfide electrolyte coarse powder.

[0140] After the calcination, the mixture was cooled naturally. At the beginning of the cooling, the carrier gas was replaced from pure nitrogen to a mixture of oxygen and nitrogen, with a flow rate of 1 L / min, a volume ratio of oxygen to nitrogen in the mixture of 0.3:1, and a ventilation time of 50 min. After the completion, the carrier gas was replaced with pure nitrogen until it reached room temperature. Subsequently, a stainless steel mesh with an aperture of 10 μm was used for granulation to obtain a fine powder of sulfide electrolyte (i.e., argyrodite-type sulfide electrolyte).

[0141] Embodiment 21

[0142] This embodiment provides a argyrodite-type sulfide electrolyte, whose molecular formula is Li6PS5Cl1.

[0143] The electrolytic preparation of the argyrodite-type sulfide comprises:

[0144] S1: Preparation of argyrodite-type sulfide electrolyte precursor.

[0145] Weigh a total of 10 g of Li2S powder, P2S5 powder and LiCl powder as a raw material for preparation, and make the molar ratio of Li2S powder, P2S5 powder and LiCl powder in the raw material for preparation be 2.5:0.5:1 according to the molar ratio of the elements in the molecular formula Li6PS5Cl1. Accordingly, the mass percentage of Li2S powder in the raw material for preparation is 42.77%, the mass percentage of P2S5 powder in the raw material for preparation is 41.43%, and the mass percentage of LiCl powder in the raw material for preparation is 15.80%.

[0146] The raw materials were loaded into a ball mill, the mass ratio of the raw materials to the ZrO2 ball mill was 1:40, and a mixture of hydrogen sulfide and argon (the volume ratio of hydrogen sulfide to argon was 1:10) was introduced into the ball mill. The ball mill speed was 500 rpm, and the ball mill was paused for 30 minutes every 5 hours, and the material was collected after a total of 40 hours of ball milling.

[0147] The entire process of preparing the above ingredients and ball milling is completed in a glove box with a water content of less than 0.1 ppm and an oxygen content of less than 1 ppm.

[0148] All the precursor raw materials collected were placed in a high-speed crusher for crushing. The threaded blades in the crusher cavity rotated at high speed, and the blade speed was controlled to be 21000rpm. After every 10 minutes of crushing, there was a 30-minute pause, and the total crushing time was 30 minutes (the whole crushing process was completed in a glove box with a water content of less than 0.1ppm and an oxygen content of less than 1ppm). The dry materials that were finally crushed were collected and placed in a glove box. After ensuring that the water content in the glove box was less than 0.1ppm for at least one hour, they were flattened in an open quartz crucible.

[0149] S2: calcining the argyrodite-type sulfide electrolyte precursor.

[0150] The quartz crucible in S1 was transferred from the glove box to a tube furnace for high-temperature calcination in the tube furnace. A mixed gas of hydrogen sulfide and argon was introduced into the tube furnace at 1 L / min, and the temperature was raised to 938°C at a heating rate of 190°C / h, and the temperature was kept for 4 hours to obtain a sulfide electrolyte coarse powder.

[0151] S3: Cooling the sulfide electrolyte coarse powder.

[0152] After the calcination, it is cooled naturally. When the temperature drops to 400°C, the carrier gas is replaced by a mixture of pure hydrogen sulfide and argon with a mixture of oxygen, hydrogen sulfide and argon, with a flow rate of 1L / min, and the volume ratio of oxygen to hydrogen sulfide and argon in the mixture is 0.2:1. The ventilation time is 60min, and after the end, the carrier gas is replaced with a mixture of pure hydrogen sulfide and argon until it drops to room temperature. It is then vacuum dried at 85°C for 20h, and then granulated with a stainless steel mesh with an aperture of 20μm to obtain a fine powder of sulfide electrolyte (i.e., argyrodite-type sulfide electrolyte).

[0153] Comparative Example 1

[0154] The difference between this comparative example and Example 1 is that the entire cooling process is carried out under pure argon conditions.

[0155] Comparative Example 2

[0156] The difference between this comparative example and Example 1 is that in S1, the ball milling process is carried out in a pure oxygen atmosphere.

[0157] Comparative Example 3

[0158] The difference between this comparative example and Example 1 is that in S2, the calcination temperature is 1000°C.

[0159] Comparative Example 4

[0160] The difference between this comparative example and Example 1 is that in S2, the roasting time is 3 h.

[0161] Comparative Example 5

[0162] The difference between this comparative example and Example 1 is that in S2, the roasting time is 6 hours.

[0163] Comparative Example 6

[0164] The difference between this comparative example and Example 1 is that in S2, the heating rate during the calcination process is 220°C / h.

[0165] Test example

[0166] The sulfide electrolytes obtained in Examples 1 to 19 and Comparative Examples 1 to 6 were tested for hydrogen sulfide (H2S) release, ion conductivity, and impurity (LiCl) content. The results are shown in Tables 1, 2, and Figure 1 and Figure 2 shown.

[0167] ① Hydrogen sulfide (H2S) release test:

[0168] Under argon atmosphere, weigh 0.5g of sulfide electrolyte powder, place it in a rectangular groove with a bottom area of ​​4cm×4cm in the tank, and seal it in a sealed glass cover under the dry room environment, where the dry room environment controls the dew point at -45℃ and the temperature at 22℃. The inner size of the glass cover is 24cm×19cm×14cm. A small fan is also placed in the glass cover to ensure uniform air composition in the cover, and a hydrogen sulfide detection instrument is placed to record the total amount of H2S released after standing for 30 minutes. The amount of hydrogen sulfide released in Table 1 is calculated as the volume of hydrogen sulfide produced when 1g of sulfide electrolyte is exposed for 30 minutes.

[0169] ②, Ionic conductivity test:

[0170] The sulfide electrolyte before and after exposure to the dry room environment was placed in a glove box with a water content of less than 0.1ppm, and was unidirectionally pressed at a pressure of 220MPa to form an electrolyte sheet with a diameter of 10mm and a thickness of about 2mm. After placing a certain degree of flexibility on both ends of the electrolyte sheet, it was pressed in both directions at a pressure of 60MPa once, and then the pressure was released to assemble a blocked electrode battery. Subsequently, the blocked electrode battery was subjected to an AC impedance test, and the conductivity was calculated according to the formula σ=L / RS, where σ is the conductivity, in Siemens per meter (S / m) or millisiemens per centimeter (mS / cm); L is the thickness of the electrolyte sheet, in meters (m); R is the resistance of the EIS test, in ohms (Ω); S is the cross-sectional area, in square meters (m2). 2 ).

[0171] ③. Impurity (LiCl) content test:

[0172] The peak area parameters of LPSX phase (Li7PS6, PDF No. 34-0688) and LiCl phase (PDF No. 04-0664) in each group of materials were obtained by using the Pearson Ⅶ chemometric peak separation program in the X-ray diffraction data processing system software, and the mass fraction of LiCl impurity phase in the fired material was calculated by the K value method.

[0173] Table 1 Hydrogen sulfide release, ionic conductivity change and LiCl content results of some sulfide electrolytes

[0174] Group <![CDATA[O2:Ar]]> Ventilation duration <![CDATA[H2S release amount]]> Initial ionic conductivity Ionic conductivity after exposure LiCl content Example 1 1:10 5min 0.03 8.3 6.7 0.5% Example 2 1:10 10min 0.06 7.1 6.3 0.8% Example 3 1:10 20min 0.05 6.2 5.4 0.6% Example 4 1:5 5min 0.06 6.4 5.5 0.8% Example 5 1:5 10min 0.05 5.9 5.1 0.6% Example 6 1:5 20min 0.07 5.1 4.5 0.9% Comparative Example 1 0 none 0.12 2.5 0.3 3.9%

[0175] Combining Table 1 and Figure 1 as well as Figure 2 It can be seen that when the argyrodite-type sulfide electrolyte provided in Examples 1 to 6 of the present invention is exposed in a drying chamber, less hydrogen sulfide is produced, and the ionic conductivity retention rate after exposure is high, and the problem of high LiCl impurity content in the chlorine-rich system can be effectively solved. When a mixed gas of argon and oxygen is introduced for a short time during the cooling stage, the amount of hydrogen sulfide released by the material is small, the initial conductivity can be maintained at a high level, and the conductivity retention rate after exposure is high, and the LiCl impurity content can be reduced to below 1%. When the time for introducing the mixed gas is extended or the proportion of oxygen in the mixed gas is increased, the amount of hydrogen sulfide released and the LiCl impurity content can be further reduced, but the initial conductivity of the fired material is low at this time.

[0176] Table 2 Hydrogen sulfide release, ionic conductivity change and LiCl content results of some sulfide electrolytes

[0177] Group <![CDATA[H2S release amount]]> Initial ionic conductivity Ionic conductivity after exposure LiCl content Example 7 0.08 5.5 3.2 1.5% Example 8 0.07 6.3 4.2 1.8% Example 9 0.07 6.0 4.3 1.0% Example 10 0.09 5.3 3.6 1.7% Embodiment 11 0.05 5.3 1.3 1.5% Example 12 0.11 3.4 0.8 1.6% Embodiment 13 0.08 3.4 3.1 1.2% Embodiment 14 0.09 3.3 3.1 1.3% Embodiment 15 0.10 3.8 2.9 1.0% Example 16 0.07 3.9 3.2 1.5% Embodiment 17 0.06 3.7 3.1 1.4% Embodiment 18 0.05 3.5 3.1 1.5% Embodiment 19 0.05 3.1 2.9 1.8% Comparative Example 2 0.20 2.7 0.8 3.5% Comparative Example 3 0.29 2.3 0.3 5.3% Comparative Example 4 0.16 2.7 0.6 4.5% Comparative Example 5 0.13 2.1 0.8 4.2% Comparative Example 6 0.15 2.6 1.1 3.8%

[0178] It can be seen from Table 2 that the sulfide electrolyte provided in the embodiment of the present invention has higher air stability, conductivity and phase purity than the sulfide electrolyte provided in the comparative example.

[0179] In summary, the sulfide electrolyte preparation method provided by the present invention can oxidize the active sulfur on the surface of the sulfide particles by setting the atmosphere of at least part of the cooling stage to an oxygen-containing atmosphere, thereby increasing the oxygen content on the surface of the particles. At the same time, the above method can inhibit the precipitation of LiCl during the cooling process, and the phase purity of the material can be improved. In addition, the active sulfur at positions 4a and 4d on the particle surface reacts with oxygen during the cooling process, and the water resistance and oxidation resistance of the material can be improved. Even if it is treated in a dry environment, the material deteriorates less, so that the assembly operation of the all-solid-state secondary battery can be directly performed in a dry environment. The obtained sulfide electrolyte has high air stability, conductivity and phase purity, and can be used to prepare all-solid-state batteries with high energy density and conductivity.

[0180] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a sulfide electrolyte, characterized in that: The following steps are involved: After the argyrodite-type sulfide electrolyte precursor is calcined, the sulfide electrolyte material obtained by the calcination is subjected to a cooling treatment, and during the cooling treatment, the atmosphere corresponding to at least part of the cooling stage is set to an oxygen-containing atmosphere; The calcination temperature is 290°C to 938°C; the calcination time is 4h to 5h; the heating rate during the calcination process is 180°C / h to 200°C / h; The oxygen-containing atmosphere is a mixed gas atmosphere of oxygen and inert gas; in the mixed gas, the volume ratio of oxygen to inert gas is 0.05:1 to 0.5:1; and the ventilation time of the oxygen-containing atmosphere is 1 min to 60 min.

2. The preparation method according to claim 1, characterized in that: The preparation of the argyrodite-type sulfide electrolyte precursor comprises: mixing the preparation raw materials under a first inert atmosphere and ball milling; wherein the preparation raw materials comprise Li2S, P2S5 and LiX, where X is a halogen element.

3. The preparation method according to claim 2, characterized in that: X includes at least one of Cl, Br and I.

4. The preparation method according to claim 2, characterized in that: The first inert atmosphere includes a nitrogen atmosphere, an argon atmosphere, and a mixed atmosphere of hydrogen sulfide and argon.

5. The preparation method according to claim 4, characterized in that: The first inert atmosphere is an argon atmosphere.

6. The preparation method according to claim 2, characterized in that: The mass percentage of the Li2S in the raw material is 30% to 45%, the mass percentage of the P2S5 in the raw material is 40% to 45%, and the mass percentage of the LiX in the raw material is 15% to 30%.

7. The preparation method according to claim 6, characterized in that: The molar ratio of the Li2S, the P2S5 and the LiX is 1.9:0.5:1.

6.

8. The preparation method according to claim 2, characterized in that: The rotation speed of the ball mill is 200 rpm to 500 rpm; and / or the time of the ball mill is 40 h to 60 h.

9. The preparation method according to claim 2, characterized in that: The calcination temperature is 450℃~550℃.

10. The preparation method according to claim 2, characterized in that: The calcination time is 4.5h.

11. The preparation method according to claim 2, characterized in that: The calcination is performed under a second inert atmosphere.

12. The preparation method according to claim 2, characterized in that: The argentite-type sulfide electrolyte precursor subjected to the calcination treatment satisfies the following requirement: the mass change of water contained in the argentite-type sulfide electrolyte precursor does not exceed 0.1 ppm for at least one consecutive hour.

13. The preparation method according to claim 1, characterized in that: The calcination temperature is at least 400° C., and during the cooling process, at least the atmosphere corresponding to the stage where the temperature does not exceed 400° C. is set to an oxygen-containing atmosphere.

14. The preparation method according to claim 13, characterized in that: During the cooling process, when the temperature drops to 380-430° C., the second inert atmosphere is adjusted to an oxygen-containing atmosphere.

15. The preparation method according to claim 1, characterized in that: The ventilation time of the oxygen-containing atmosphere is 5 minutes to 50 minutes.

16. The preparation method according to claim 1, characterized in that: In the mixed gas, the volume ratio of oxygen to inert gas is 0.1:1 to 0.3:

1.

17. The preparation method according to claim 1, characterized in that: The inert gas is argon.

18. A sulfide electrolyte, characterized in that: The sulfide electrolyte is prepared by the preparation method according to any one of claims 1 to 17.

19. An all-solid-state battery, characterized in that: The all-solid-state battery contains the sulfide electrolyte according to claim 18.

Citation Information

Patent Citations

  • Manufacturing method of sulfide solid electrolytic material

    JP2014038755A

  • METHOD FOR PRODUCING LiBON COMPLEX OXIDE

    JP2022089107A